Carsten Höller : Register. - Fondazione Prada, Milano; Celant, Germano; Hauser, Baldo; Obrist, Hans-Ulrich; Prada, Miuccia (Milano : Fondazione Prada Milano, 2000)
Published on the occasion of the Synchro System exhibition. Register comprises the whole of Carsten Höller's oeuvre in a listing going back in time from the year 2000. It is, in effect, the artist's Curriculum Vitae giving a detailed account of his exhibitions and joint and individual projects, which is partially illustrated with his own explanations.
Carsten Höller : Synchro System, Fondazione Prada, Milano, 22.XI.2000 - 7.I.2001
geboortedatum, bibliog. [3 p.]
Engels
boek
Keywords: Höller, Carsten